Effects of Lowest Bidding Bid Awarding System in Public Sector Construction Projects in Pakistan (Global Journal of Management and Business Research, 2015)
Construction industry participants have started recognizing that accepting the least price bid does not guarantee maximum value. Achieving a value-based procurement approach is a challenge, particularly for the Pakistani public sector clients, who are limited in their ability to evaluate the competitive bids based solely on the lowest-bid award system. Persisting problems of inferior quality of constructed facilities, high incidence of claims and litigation, and frequent cost and schedule overruns have become the main features of Pakistan#x2019;s public construction works contracts.
Keywords: bidding system; construction projects; public sector construction; public sector procurement